Electrochemically enabled (3+2) cycloaddition of unbiased alkenes and β-dicarbonyls - Suryawanshi, Sharad M.; Sahoo, Suman; Shaligram, Parth S.; Manna, Narugopal; Samanta, Ramesh C. (Chemical Communications, 2024)
A (3+2) cycloaddition between unbiased alkenes and 1,3-dicarbonyls is accomplished by judicious choice of electrode material and electrocatalyst to access dihydrofuran derivatives. A fluorinated porous carbon electrode with appropriate thickness governs unprecedented reactivity. This methodology eliminates the necessity for any stabilizing group within the alkene substrate. This is a rare example of the annulation of unbiased internal and terminal alkenes with cyclic and acyclic beta-dicarbonyls.
Keywords: 1; 3-DICARBONYL COMPOUNDS; DIHYDROFURANS; FACILE SYNTHESIS